Esporte adaptado e ergonomia: bancos de arremesso para atletas paralímpicos - Freire, Gilberto Martins (2018)
Performance levels of athletes with disabilities have improved significantly, and research in this area has collaborated with practitioners involved in the physical, technical, tactical, and development of equipment and artifacts to make activities feasible. The settings of frame throwers do not cooperate with the interface between the athlete and his sporting artifact. Regiments do not consider the inclusion of forms that favor sports practice. Frame throwers have recently undergone regimental changes which may hamper the design and the possibilities and functional capabilities for their users. This study aims to create an ergonomic frame thrower specific for the sports functional classes F54 and F57. The research was developed in three phases (Evaluation, Design and Testing). Four athletes who compete in the “Circuito Paraolímpico Loterias da Caixa de Atletismo”, sponsored by the Brazilian Paralympic Committee. Data collection included protocols for the evaluation of athletes, benchmarks, performance, semi-structured interview, bipolar questionnaire for musculoskeletal complaints. The software Ergolândia 5.0, Kinovea Video Editor program and IBM SPSS version 2 were used for the analysis. The athletes underwent a 6-week training routine with the usual frame thrower and later with the ergonomic one. The evaluations were performed before and after training. The customized frame thrower not only showed to be effective in reducing pain and complaints but also it allowed a change in the results. The study ended with the production of four pit banks for the functional classes from 54 to 57 that had as a characteristic the bipartite structure with specific accessories for each of the classes.